2010
DOI: 10.1073/pnas.1003111107
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms of observational learning

Abstract: Individuals can learn by interacting with the environment and experiencing a difference between predicted and obtained outcomes (prediction error). However, many species also learn by observing the actions and outcomes of others. In contrast to individual learning, observational learning cannot be based on directly experienced outcome prediction errors. Accordingly, the behavioral and neural mechanisms of learning through observation remain elusive. Here we propose that human observational learning can be expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
370
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 313 publications
(402 citation statements)
references
References 36 publications
30
370
2
Order By: Relevance
“…Learning behavior in the self, prosocial, and no one conditions was modeled using a reinforcement learning (RL) algorithm (2), which has been extensively used to examine the behavioral and neural basis of arbitrary visuomotor associations in both self and social contexts (13,(17)(18)(19). The RL model assumes that the associative value of an action (or stimulus) changes when new information reveals that the actual outcome of a decision is different from the expected outcome (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning behavior in the self, prosocial, and no one conditions was modeled using a reinforcement learning (RL) algorithm (2), which has been extensively used to examine the behavioral and neural basis of arbitrary visuomotor associations in both self and social contexts (13,(17)(18)(19). The RL model assumes that the associative value of an action (or stimulus) changes when new information reveals that the actual outcome of a decision is different from the expected outcome (2).…”
Section: Methodsmentioning
confidence: 99%
“…The ventral striatum, sgACC, dACC, and DLPFC are also implicated in processing information about rewards others will receive (12-16), PEs when interacting with others (13,(17)(18)(19), and prosocial behavior (e.g., refs. 4-7 for reviews).…”
mentioning
confidence: 99%
“…In humans, functional MRI (fMRI) studies and even in vivo surgical recordings (Zaghloul et al, 2009) have reported correlates of prediction-error signals in the striatum that resemble those of dopamine neurons recorded in animals, including phasic (event-related) positive and negative prediction error responses (McClure et al, 2003a;O'Doherty et al, 2003;D'Ardenne et al, 2008) that reflect probability (e.g. Abler et al 2006;Burke et al 2010;Spicer et al 2007;Tobler et al 2007) and more specific predictions of formal learning theories Kahnt et al, 2012;Rutledge et al, 2010;Tobler et al, 2007). However, it is worth keeping in mind that the haemodynamic response measured with neuroimaging is nonspecific rather than a one-to-one reflection of a particular neural event such as dopamine release (see also DĂŒzel et al 2009), which could explain why some fMRI studies have suggested positive coding of losses (Seymour et al 2004; although see also Tom et al 2007) and a dominance of action over value (Guitart-Masip et al, 2012 (Kamin, 1969) used an aversive between-subjects design; by contrast, the experiment described in the text and depicted in abbreviated form here (Waelti et al, 2001) used an appetitive within-subject design where the test consists of a comparison between Y and X (see also Figure 2A); The optogenetic unblocking experiment of Steinberg et al (2013) used a between-subject design.…”
Section: Phasic Dopamine Signals Represent Model-free Prediction Errorsmentioning
confidence: 99%
“…Moreover, despite the rapidly accumulating research on reward processing in social domains (13)(14)(15)(16)(17)(18)(19), the question remains of how neural representation of self-regarding vs. other-regarding values is related to individual differences in altruistic behavior.…”
mentioning
confidence: 99%